THE OFFENCE OF IDENTITY THEFT IN THE POLISH CRIMINAL LAW (ARTICLE 190A § 2 OF THE PENAL CODE). (PART TWO) - Mozgawa, Marek; Nazar, Katarzyna (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2019)
Purpose: the main purpose of the paper is to analyse the problem of provision concurrence of Art. 190a § 2 with other articles of the Penal Code, as well as to present the issues of imposing punishment for this offence and the statistical picture of the phenomenon of identity theft. Methods: to obtain these aims the dogmatic method was used as well as analysis of statistical data. Results: the offence under Art. 190a § 2 may be in real concurrence with the provisions describing offences against the protection of information (art. 265-268a, 269a of the Penal Code), against the credibility of documents (art. 270, art. 272, art. 273, art. 275 of the Penal Code) as well as with provisions describing offences against property (e.g.: art. 284 § 1, 285, 287, 288 § 1 or 2 of the Penal Code). Analysis of data referring to final convictions for the offence of identity theft shows that the punishment most often imposed is deprivation of liberty, almost always applied with the conditional suspension of its execution. Discussion: the number of discovered offences of theft identity is growing dynamically, unfortunately, however, there is no such dynamics in the case of detection of the offence. Therefore the question arises about the causes of the detection results becoming poorer every year.